Planar Heterojunction Perovskite Solar Cells Incorporating Metal-Organic Framework Nanocrystals - Chang, Ting-Hsiang; Kung, Chung-Wei; Chen, Hsin-Wei; Huang, Tzu-Yen; Kao, Sheng-Yuan; Lu, Hsin-Che; Lee, Min-Han; Boopathi, Karunakara Moorthy; Chu, Chih-Wei; Ho, Kuo-Chuan (Advanced materials (Weinheim), 2015)
Zr‐based porphyrin metal–organic framework (MOF‐525) nanocrystals with a crystal size of about 140 nm are synthesized and incorporated into perovskite solar cells. The morphology and crystallinity of the perovskite thin film are enhanced since the micropores of MOF‐525 allow the crystallization of perovskite to occur inside; this observation results in a higher cell efficiency of the obtained MOF/perovskite solar cell.